Determinan Modal Kerja pada Perusahaan Manufaktur di Bei Periode 2017 – 2023 - Azizah Suci Pratiwi; Adler Haymans Manurung; Jhonni Sinaga; Djuni Thamrin; Adi Wibowo Noor Fikri (International Forum of Researchers and Lecturers, 2024)
Working capital is to finance the company's daily operations, such as paying salaries, buying raw materials, paying transportation, paying debts, paying electricity accounts, and paying other costs. The purpose of this study is to analyze the behavior of data on profitability, liquidity, and leverage variables on working capital. Quantitative methods emphasize aspects of measurement and calculation. The manufacturing company used a research method, namely purposive sampling. The data used is secondary data sourced from the statement of financial position and profit and loss in the company's annual report. This study was conducted to determine whether each independent variable affects the dependent variable. The results of this study indicate that Profitability, Liquidity, and Leverage together (simultaneously) have a significant effect on Working Capital. Based on the results of partial panel data analysis, the Profitability variable has a negative effect on Working Capital. The Liquidity variable has a positive and significant effect on Working Capital. Leverage variable has a negative effect on Working Capital.